Psalm body help us: Hearing the lament of health care professionals - Harootunian-Cutts, Jacquelyn (Review and expositor, 2022)
The COVID-19 pandemic has led to burdensome moral distress for health care professionals in the United States. Despite being initially hailed as “heroes” by the American public, health care professionals have encountered unique barriers to healing in the context of the devastating pandemic. Unfortunately, the health care system was ill-equipped to deal with the dramatic surge in moral distress caused by the pandemic. The church, and faith-based health care systems, can play a crucial role for hearing the lament of morally distressed health care professionals and attending to them as a community toward moral reintegration. We suggest that the Psalms offer an entry point both for those who need to express their lament of moral distress and those who accompany health care professionals in seeking structural changes, advocating for needed resources for patient care, and attaining the important goal of spiritual healing.